Counseling on Cooperative Management as a Driving Force for Economic Empowerment at the Sukamiskin Islamic Boarding School Bandung - Kartawinata, Budi Rustandi; Akbar, Aldi; Hidayat, Agus Maolana; Witarsyah, Deden; Hamami, Faqih; Pratiwi, Oktaria Nurul; Ahmad, Mokhtarrudin; Zahid, Azham; Sujak, Aznul Fazrin bin Abu; Razali, Raja Razana Raja; Mangsor, Miza (PT. Riset Press International, 2024)
This Community Service aims to provide understanding to cooperative administrators and students at the Sukamiskin Islamic Boarding School regarding the benefits and effective management strategies of cooperatives. The method used in this research is interviews and direct observation of cooperative administrators and students involved in cooperative activities. The research results show that counseling about cooperative management is very important to increase the understanding and skills of cooperative administrators and students in managing cooperatives. In this outreach, information and training is provided regarding the basic principles of cooperative management, financial planning, risk management and marketing of cooperative products. With this outreach, it is hoped that cooperative management at the Sukamiskin Islamic Boarding School can become more effective and have a positive impact on community economic empowerment. Cooperative administrators and students will become more competent in managing cooperatives, so that they can generate better income for their members. Counseling on cooperative management as a driving force for economic empowerment at the Sukamiskin Islamic Boarding School, Bandung City is very important to increase the understanding and skills of cooperative administrators and students in managing cooperatives. It is hoped that this counseling can provide significant benefits in increasing the income and welfare of cooperative members.